2015
DOI: 10.1063/1.4935372
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-N2 assisted growth of 5-20 nm thick β-W films

Abstract: A technique to deposit 5-20 nm thick β-phase W using a 2-second periodic pulse of 1 sccm-N2 gas on Si(001) and SiN(5 nm)/Si(001) substrates is reported. Resistivity, X-ray photoelectron spectroscopy and X-ray reflectivity were utilized to determine phase, bonding and thickness, respectively. X-ray diffraction patterns were utilized to determine the crystal structure, lattice constant and crystal size using the LeBail method. The flow rate of Nitrogen gas (continuous vs. pulsing) had significant impact upon the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Fig. 5a shows a peak at 29.7 eV related to the W metal element, while Narasimham et al [25] found it at about 30.5 eV to 31.3 eV which is close to the obtained results. Also, the spectra present a symmetrical peak of W 4f incorporated with WO 3 (W 4f 7/2 (35.6 eV)) and (W 4f 5/2 (36.7 eV)).…”
Section: Edx and Xps Studysupporting
confidence: 87%
“…Fig. 5a shows a peak at 29.7 eV related to the W metal element, while Narasimham et al [25] found it at about 30.5 eV to 31.3 eV which is close to the obtained results. Also, the spectra present a symmetrical peak of W 4f incorporated with WO 3 (W 4f 7/2 (35.6 eV)) and (W 4f 5/2 (36.7 eV)).…”
Section: Edx and Xps Studysupporting
confidence: 87%
“…2(a) (purple curve), strongly limiting the use of seed and adhesion materials. However, there are reports showing that the presence of oxygen or nitrogen adsorbed onto the surface provides nucleation sites for the growth of metastable β-W [37][38][39].…”
Section: Extension Of Tungsten β Phase Windowmentioning
confidence: 99%
“…Such thin layers impose severe constraints on the choice of thickness and on the etching conditions, possibly leading to a strong distribution of the SOT resistance and efficiency from device to device. We report in this paper the possibility of optimizing the growth of β-W using dopants such as nitrogen and oxygen [37][38][39]. We develop a process in which growing a bilayer of oxygen-and nitrogendoped tungsten, W(O, N), results in process control of the tungsten β phase to more than 10 nm, while concurrently improving the PMA as well as improving the SOT efficiency to −44.4%.…”
Section: Introductionmentioning
confidence: 99%
“…This disparity in spin Hall angles for the different phases has led to recent work 5,6 to resolve the origin of the high spin Hall angle in β-W. Since the growth of β-W requires the addition of O [7][8][9] , N 10,11 , F 12,13 , or Si 14 impurities to stabilize the crystal lattice, it has been unclear if the high spin Hall angle was intrinsic or extrinsic. The intrinsic spin Hall effect is due to strong relativistic spin-orbit interactions in the material that act to separate spins and produce a transverse spin current when a charge current is applied.…”
Section: Introductionmentioning
confidence: 99%